A Systematic Study of the Influence of Workplace Dynamics on Employee Job Satisfaction: Evidence from India - Rohit, Tejas R.; A. Dadhich, Meghashree; Singh, Shyamsunder; Tandon, Aarti Antarix; Vadhavi, Shital P (Journal of Neonatal Surgery, 2025)
In today’s competitive business landscape, organizations must prioritize employee satisfaction to sustain productivity and innovation. This study examines the relationship between working environment and job satisfaction in India, focusing on the education, banking, and telecommunications sectors. A quantitative approach was adopted, utilizing a validated survey questionnaire distributed to 210 employees through simple random sampling. Results revealed a statistically significant positive correlation between conducive working environments and job satisfaction. Key factors such as top management support, job safety, and work-life balance emerged as critical drivers of employee contentment. The findings emphasize the need for organizations to foster supportive workplaces to enhance employee loyalty, productivity, and organizational success.